LncRNA NEAT1 Promotes High Glucose-Induced Mesangial Cell Hypertrophy by Targeting miR-222-3p/CDKN1B Axis - Liao, Lin; Chen, Jie; Zhang, Chuanfu; Guo, Yue; Liu, Weiwei; Liu, Wenrui; Duan, Lianxiang; Liu, Ziyang; Hu, Jing; Lu, Jianrao (Frontiers in Molecular Biosciences, 2021)
Glomerular hypertrophy is an early morphological alteration in diabetic nephropathy. Cyclin-Dependent Kinases have been shown to be required for high glucose (HG)-induced hypertrophy; however, the upstream regulators of CDKN1B in glomerular hypertrophy remain unclear. Herein we describe a novel pathway in which Long noncoding RNA (lncRNA) NEAT1 regulates the progression of mesangial cell hypertrophy via a competing endogenous RNA (ceRNA) mechanism. Real-time PCR was performed to detect the relative NEAT1 and miR-222-3p expressions and further confirmed the relationship between NEAT1 and miR-222-3p. Cell cycle was evaluated by flow cytometry. The related mechanisms were explored by Western blot, RNA immunoprecipitation and chromatin immunoprecipitation assay. We show that NEAT1 forms double stranded RNA (dsRNA) with miR-222-3p, thus limiting miR-222-3p’s binding with CDKN1B. This release of CDKN1B mRNA leads to elevated CDKN1B protein expression, resulting in hypertrophy. In addition, we demonstrated that STAT3 which is activated by HG induces the transcription of NEAT1 by binding to its promoter. Our findings underscore an unexpected role of lncRNAs on gene regulation and introduce a new mode of proliferation regulation in mesangial cells.